Mobile Game Design for Learning Chemical Bonds with Endless Run Approach - Hafis, Muhammad; Supianto, Ahmad Afif (International Journal of Interactive Mobile Technologies (iJIM), 2018)
This research focuses on the design of a mobile application game that uses endless run method to learn chemistry concept of chemical bonds, its design is analyzed thoroughly. Application-based learning is one of the method of learning that has been proven to be effective, however, previous studies focuses on the elements of serious gaming that neglects the fun elements in the game itself, disdaining the nature of a game. This research aims to discover the relevance of player happiness and fun level based when playing an educational game and its correlation with the level of learning while also focuses on understanding what hinders a player in the context of chemistry-based games. The testing planning are exposed along with a hypothesis that player happiness positively correlates with its level of learning, while the hindrance can be identified by using statistical approach.